Relationship between Economic Growth and Electricity Consumption in India: A Re-Investigation - Nath, Smita (Energy Economics Letters, 2020)
This paper attempts to re-examine the relationship between economic growth and electricity consumption in India for the period 1971-72 – 2016-17 for the country as a whole and for the agricultural and industrial sectors separately. Using gross value added (GVA) and per capita net national product (NNP) as indicators of economic growth techniques like cointegration, error correction model and Granger causality tests are applied for the study. The results indicate that there is a long run positive relationship between economic growth and electricity consumption when GVA is the indicator of growth. However, the short run coefficients are not statistically significant. Per capita NNP does not have any long run relationship with per capita electricity consumption but there is a unidirectional Granger-cause from log per capita NNP to log per capita electricity consumption when lag length is three. There is unidirectional Granger-causality from log GVA to log electricity consumption in the agricultural sector also. For the industrial sector, however, neither variable Granger causes the other. The cross section analysis for thirty two states and union territories of India reveals that per capita net state domestic product (NSDP) positively and significantly affects per capita electricity consumption of states in each of the years from 2012-13 to 2016-17. But the responsiveness of electricity consumption with respect to NSDP declines over the years.